2018
DOI: 10.7717/peerj.4154
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic risk and preventive measures of musculoskeletal disorders in the dentistry environment: an umbrella review

Abstract: IntroductionDental practitioners are exposed to different occupational hazards during the course of their professional activity, such as physical, chemical, biological, ergonomic factors. The ergonomic hazards, caused by strained posture and prolonged repetitive movements, can induce musculoskeletal disorders. It occurs in 54–93% of dental professionals and involve the spine, shoulder and hand-wrist tract. Through a systematic review of international literature, we analyzed specific ergonomic risk factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 29 publications
(31 reference statements)
1
44
0
6
Order By: Relevance
“…Serval studies have discussed specific ergonomic risk factors and preventive measures in the dentistry field . However, among the students that participated in the present study only 14% reported that they received ergonomic education, and the numbers were higher among the experienced dental hygienists but were still relatively low (40%).…”
Section: Discussionmentioning
confidence: 98%
“…Serval studies have discussed specific ergonomic risk factors and preventive measures in the dentistry field . However, among the students that participated in the present study only 14% reported that they received ergonomic education, and the numbers were higher among the experienced dental hygienists but were still relatively low (40%).…”
Section: Discussionmentioning
confidence: 98%
“…Muskuloskeletni poremećaji su jedno od najčešćih oboljenja koje nastaje kao posledica rada kod većine zdravstvenih radnika, a naročito stomatologa. Postoji više faktora koji dovode do muskuloskeletnih poremećaja kod stomatologa [4]: neprekidno kretanje, nedovoljno osvetljenja, nepravilno držanje tela tokom rada, psihološki stres, genetika, fizički uslovi, starost i težina [5,6].…”
Section: Uvodunclassified
“…Musculoskeletal disorders are one of the most common types of work-related diseases that affect health workers, especially dentists. There are multiple factors that contribute to development of musculoskeletal disorders among dentists [4]: continuous movements, insufficient lighting, improper body position during work, psychological stress, genetics, physical conditions, age and weight [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Workrelated musculoskeletal disorders have been reported as the most important reason for early retirement among dentists, among which the lower back pain (LBP) is the most prevalent [2,3]. The main reason for undesirable and non-ergonomic positions among dentists is with the aim of achieving an ideal view of the patient's mouth and providing a comfortable position for the patient [1,4].…”
Section: Introductionmentioning
confidence: 99%